2021
DOI: 10.1016/j.clim.2020.108642
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral immunological features of COVID-19 patients in Taizhou, China: A retrospective study

Abstract: Background Abnormal peripheral immunological features are associated with the progression of coronavirus disease 2019 (COVID-19). Methods Clinical and laboratory data were retrieved in a cohort of 146 laboratory-confirmed COVID-19 patients. Potential risk factors for the development of severe COVID-19 were evaluated. Results On admission, lymphocytes, CD3+, CD4+ and CD8+ T cells, eosinophils, and albumin and pre-albumin were dramatically lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
4
3
0
Order By: Relevance
“…Our study identified that the majority of these well-known pathophysiological elements were associated with disease-related MN in COVID-19 patients, and included older age; anorexia and reduced food intake; respiratory failure; fever during the viral response phase; and catabolic changes due the host inflammatory response phase (increased ferritin and CRP levels, tocilizumab treatment, and higher disease severity). In addition, we observed a considerable reduction in muscle mass and visceral protein markers (albumin, total lymphocytes and cholesterol) at admission, as reported in other studies [41,67]. At discharge, we found significant improvements in levels of CRP, ferritin and T lymphocytes [41,67] and in some nutritional biomarkers that could be related to the favorable progression of the disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study identified that the majority of these well-known pathophysiological elements were associated with disease-related MN in COVID-19 patients, and included older age; anorexia and reduced food intake; respiratory failure; fever during the viral response phase; and catabolic changes due the host inflammatory response phase (increased ferritin and CRP levels, tocilizumab treatment, and higher disease severity). In addition, we observed a considerable reduction in muscle mass and visceral protein markers (albumin, total lymphocytes and cholesterol) at admission, as reported in other studies [41,67]. At discharge, we found significant improvements in levels of CRP, ferritin and T lymphocytes [41,67] and in some nutritional biomarkers that could be related to the favorable progression of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, we observed a considerable reduction in muscle mass and visceral protein markers (albumin, total lymphocytes and cholesterol) at admission, as reported in other studies [41,67]. At discharge, we found significant improvements in levels of CRP, ferritin and T lymphocytes [41,67] and in some nutritional biomarkers that could be related to the favorable progression of the disease. Our contribution here is the identification of OD at admission as an independent factor for MN during hospitalization of COVID-19 patients.…”
Section: Discussionsupporting
confidence: 87%
“…Longitudinal observation of immune indicators in recovered patients showed that compared with the 2-week follow-up after discharge, lymphocytes and lymphocyte subsets increased, cytokines decreased, and complement series decreased to normal levels at one-year follow-up, except for the abnormal CT group. This is an addition to previous studies reporting that the immune system gradually recovered to a steady state after two weeks of discharge [7] , [17] , [18] , and also reflects the need for long-term follow-up. Interestingly, compared with healthy controls, the normal group had higher NK cell count levels at one-year follow-up, which also suggested that NK cells were a prognostic factor for good recovery of lung function [13] .…”
Section: Discussionsupporting
confidence: 62%
“…There is evidence that complement activation is the pathophysiological basis of many lung diseases, such as asthma and acute respiratory distress syndrome [5] , and also leads to immune-mediated lung injury [6] . Normal immune status was found among COVID-19 recovered subjects 2 weeks after the discharge [7] . However, the long-term immune status of COIVD-19 patients has not been reported in the literature.…”
Section: Introductionmentioning
confidence: 83%
“…Our previous studies revealed that total lymphocytes, CD3+, CD4+, and CD8+ T cells were dramatically lower among patients with severe COVID-19 than among non-severe patients at admission. These cells returned to normal levels by the second week after discharge, however, lower CD8+ T cell count is an independent risk factor for longer viral positivity duration and is related to an increased risk for discharged patients with SARS-CoV-2 re-positivity ( 9 11 ). Pro-inflammatory cytokines and chemokines, such as interleukin (IL)-1β, IL-6, IL-8, tumour necrosis factor (TNF)-α, macrophage inflammatory protein (MIP) 1α/CCL3, interferon (IFN)-γ-induced protein 10 (IP10), monocyte chemoattractant protein 1 (MCP1), granulocyte colony-stimulating factor (G-CSF), and granulocyte-macrophage colony-stimulating factor (GM-CSF), were substantially increased ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 94%